Global accounting convergence: Quality, acceptability and enforceability of IFRS in Nigeria - Rimi, Mohammed Lawal Dan (2013)
In view of the pressing demands to converge with IFRS as the international accounting benchmark and to serve as common global accounting language, coupled with the concerns expressed by critics over its uniform suitability and relevance in diverse economic, political and institutional settings across the globe, it is increasingly significant to empirically investigate; the quality, acceptability and enforceability of the International Financial Reporting Standards (IFRS) in countries of different settings. Therefore, this study investigates the perception of financial reporting users and preparers on global accounting convergence in terms of IFRS quality, IFRS acceptability and IFRS enforceability in Nigeria. Data was collected using online and self-administered survey approach. Based on the empirical findings, it was concluded that despite the possible issues and challenges associated with convergence to IFRS, it could yet be considered as a right step, in a right direction and at a right time for Nigeria. Convergence to IFRS is in the best interest of the country in order to tap its full economic potential and her deserving leadership within the global financial market. It has been proven that convergence to IFRS has positive impact to the country's reporting system with improvement in reporting quality leading to reduction in income smoothing, and increased in value relevance of reported income